2004
DOI: 10.1007/s10194-004-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of migraine as a function of definition

Abstract: The objective was to examine the main genetic and environmental architecture of migraine in the Screening Across Lifetime of Twin (SALT) Study as a function of definition. We performed a quantitative genetic study of the Swedish population and a total of 12,095 twin pairs aged 41–64 years were interviewed on the telephone by trained lay personnel using a structured questionnaire. Lifetime assessment of recurrent headache and two measures of migraine were obtained, diagnosis in line with the 1988 International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The presence or absence of clinical characteristics of migraine headache in our patients, including unilateral location, throbbing quality, association of headache with nausea or vomiting, photophobia or sonophobia, osmophobia, presence of aura, family history of migraine, aggravation of headache attacks during the menstrual period and typical demographics, were recorded by the headache specialists. 6 The likelihood ratio (LR) of these clinical migraine characteristics was analyzed in pediatric and adult groups of headache patients. 5 Patients younger than 15 years were categorized as pediatric.…”
Section: Part Imentioning
confidence: 99%
“…The presence or absence of clinical characteristics of migraine headache in our patients, including unilateral location, throbbing quality, association of headache with nausea or vomiting, photophobia or sonophobia, osmophobia, presence of aura, family history of migraine, aggravation of headache attacks during the menstrual period and typical demographics, were recorded by the headache specialists. 6 The likelihood ratio (LR) of these clinical migraine characteristics was analyzed in pediatric and adult groups of headache patients. 5 Patients younger than 15 years were categorized as pediatric.…”
Section: Part Imentioning
confidence: 99%
“…Subjects who endorsed any of these items about pain (ie, possible rheumatoid arthritis, prolonged joint pain, and osteoarthritis) were considered to have joint pain. Migraine and tension-type headache were assessed for subjects younger than 65 years with an algorithm 13 in line with the International Headache Society criteria.…”
Section: Measures For Comorbiditiesmentioning
confidence: 99%
“…Numerous researchers have shown that there is a significant genetic component to risk of this disorder (Ziegler et al 1998;Mulder et al 2003;Svensson et al 2003Svensson et al , 2004Nyholt et al 2004Nyholt et al , 2005, with estimates of heritability ranging between 34 and 57% in twin-cohort studies across six countries (Mulder et al 2003). The diagnosis of migraine is found to be difficult due to lack of biological markers and overlap with other types of neurological disorders, such as tension type headache and brain tumour.…”
Section: Introductionmentioning
confidence: 97%